Uhlelo Lwekhompyutha LwePython Kanye Nekhophasi YesiZulu Njengezinsiza Zokuthuthukisa Kanye Nokuphusisa Ulimi LwesiZulu. - Buthelezi, Mthuli (Alternation)
The Python programming language is used to write mobile and computer software programs. This popular programming language has been used in linguistics where research into human languages takes place. Most computer software programs are written using such programming languages as Python. Most human languages of the world have been analysed and described using computer tools that are compatible with Python. However, within the realm of computation not much work has been done to analyse and describe resourcescarce languages such as isiZulu. This study seeks to inspire work on using programming languages such as Python to analyse and provide descriptions of isiZulu within the context of computation. Examples of how to analyse isiZulu using Python are shown in this article, Further, analysing isiZulu within computation entails the development and thus intellectualisation of the language. Corpora play an important role as datasets in a data-driven, statistical-based model of machine learning. Therefore, the concept of a corpus has been adopted as a theoretical frameworkin this study. Within the framework of a corpus, Python tools are applied to isiZulu and its selected text samples. Contextualising the analyses and the descriptions of isiZulu to computation will assist in the development and intellectualisation of this language.